Successful treatment with tacrolimus of refractory pyoderma gangrenosum with pouchitis after restorative proctocolectomy for ulcerative colitis. Issue 3 (3rd July 2018) - Satake, Miwa; Sakuraba, Hirotake; Hiraga, Hiroto; Tarakita, Natsumi; Akemoto, Yui; Ota, Shinji; Hasui, Keisuke; Nishiya, Daisuke; Hayamizu, Shiro; Kikuchi, Hidezumi; Sawaya, Manabu; Chinda, Daisuke; et al.
Abstract: We describe herein a case of severe relapsed pyoderma gangrenosum (PG) concomitantly with severe pouchitis treated by tacrolimus. A 25-year-old woman had undergone proctocolectomy with construction of ileo-anal pouch surgery for refractory ulcerative colitis (UC). She first developed PG with refractory pouchitis, and infliximab (IFX) was administered to induce remission due to resistance to glucocorticoid therapy. After achieving remission, IFX was stopped. Five years later, severe skin ulcers concomitantly with severe pouchitis recurred and treatment with 30 mg oral prednisolone (PSL) combined with topical tacrolimus showed partial improvement. When PSL was tapered to 15 mg, the skin ulcers and diarrhea aggravated. Endoscopy revealed multiple ulcers in the ileal pouch. Treatment with oral tacrolimus was initiated for severe pouchitis and refractory PG. Forty days later, all skin ulcers became scars and multiple ulcers in the ileal pouch were also improved. Our case suggests that oral tacrolimus treatment could be a valuable treatment option for UC patients with refractory PG and pouchitis.